Investigation of the simultaneous effect of resistance training and atorvastatin in improving nonalcoholic fatty liver disease in Wistar rats fed high high-fat/fructose diet - Raouf Moradian; Amir Haji Ghasem; Saleh Rahmati; Lida Moradi (Medical Laboratory Journal)
Background: Non-alcoholic fatty liver disease (NAFLD), a highly prevalent and chronic liver disease, is characterized by a diverse range of conditions that span across a broad spectrum. Engaging in consistent physical activity has proven to be a successful method in effectively managing NAFLD, as it has demonstrated the ability to enhance crucial elements implicated in the development of the condition. Methods: Twenty-one male Wistar rats were divided into three groups: 1. NAFLD, 2. NAFLD + resistance training (RT), and 3. NAFLD + RT + atorvastatin (ATO). The groups received high-fat/fructose diet (HFFD) to induce NAFLD and it was confirmed through evaluation of histopathological analysis (H&E staining) and measurement of aminotransferase enzymes. ATO was administrated at a dose of 2 mg/kg/day. The interventions were carried out over eight weeks. Results: Triglyceride (TG), Alanine transaminase (ALT), and aspartate transaminase (AST) were significantly reduced in the NAFLD + RT + ATO group. Additionally, low-density lipoprotein (LDL) levels were lower in NAFLD + RT group than NAFLD + RT + ATO group. Alkaline phosphatase (ALP) was reduced in both NAFLD + RT and NAFLD + RT + ATO groups compared to NAFLD. There was no significant difference in weight between the groups except the first, second, and fourth weeks. Conclusion: Resistance training in combination with the administration of ATO can be deemed as an efficacious and supplementary strategy to effectively control and address NAFLD.